1986
DOI: 10.1111/j.1365-2672.1986.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide sensitivity of cold‐shocked Salmonella typhimurium and Escherichia coli and its relationship to minimal medium recovery

Abstract: Cold-shocked Salmonella typhimurium displayed minimal medium recovery (MMR), viable counts on M9 minimal agar being much higher than those on tryptone soya yeast extract agar (TSYA). The addition of catalase to TSYA restored counts to the level found on M9 agar. Peroxide concentrations between 12 and 30 mumol/l were measured in TSYB but none was detected in M9 medium. Cold-shocked cells were sensitive to reagent hydrogen peroxide at a concentration similar to that found in TSYB. The minimal medium recovery phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…S2 in the supplemental material) but not in LB medium (see Fig. S2 in the supplemental material), a finding previously reported in E. coli (51,52). The reason for the decreased catalase activity in M9 medium remains unclear.…”
Section: Figsupporting
confidence: 67%
See 1 more Smart Citation
“…S2 in the supplemental material) but not in LB medium (see Fig. S2 in the supplemental material), a finding previously reported in E. coli (51,52). The reason for the decreased catalase activity in M9 medium remains unclear.…”
Section: Figsupporting
confidence: 67%
“…As iron limitation can significantly reduce catalase activity (68), this may explain the decreased wildtype catalase levels in M9 minimal medium. Furthermore, it has also been reported that catalase activity in E. coli decreases during growth in M9 medium, possibly due to glucose-mediated catabolite repression (51,52). Whether catabolite repression of catalases also occurs in P. aeruginosa remains unknown.…”
Section: Figmentioning
confidence: 99%
“…The concentration of peroxide in 10 samples of autoclaved TSB ranged from 12 to 30 PM with a mean of 20 p~. No peroxide was detected in M9 medium (Mackey & Derrick, 1986). Loss of viability of heat-injured E. coli p3478 in M9 plus 25pM-hydrogen peroxide followed a similar course to that in TSB (Fig.…”
Section: Eflect Of Catalase On Viable Countsmentioning
confidence: 70%
“…The poor recovery of UV-irradiated cells on rich growth medium was due to inhibition of this repair mechanism by amino acids. Mackey and Derrick (1986) found that cold-shocked S. typhinlurium displayed minimalmedium recovery but that addition of catalase to the rich medium restored. counts to the level found on the minimal medium.…”
Section: Microbial Recovery and Stress Responsesmentioning
confidence: 96%